Extraction of Cu(II) Complex in Water Samples on C18 Modified N,N'-Bis(3,5-di-tert-butylsalicylidene)-1,2-diaminoethane and Its Determination by UV-VIS Spectrometry - Shojai, Mostafa; Moghimi, Ali; Tajik, Mohammad (Asian Journal of Chemistry, 2013)
A simple method has been developed for the preconcentration of copper(II) based on the adsorption of its N,N'-bis(3,5-di-tert-butylsalicylidene)-1,2-diaminoethane (H2L2) complex on a neutral C18 column. The influence of acidity, eluting agents, stability of the column, sample volume and interfering ions has been investigated. The adsorbed complex could be eluted using environmentally benign polyethylene glycol (PEG 400) and the concentration of copper(II) was determined by visible spectrophotometry at 590 nm. A detection limit of 6 μg L-1 could be achieved and the developed procedure was successfully applied for the determination of copper(II) in spiked water samples. The preconcentration factor attainable for quantitative recovery (> 97 %) of copper(II) was 100 for a 1000 mL sample volume.